2019
DOI: 10.1002/sd.1944
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of conflicts and trade‐offs: A challenge for the policy integration of the United Nations Sustainable Development Goals

Abstract: The United Nations Sustainable Development Goal (SDG) agenda compels nations to face challenges, especially interministerial conflicts, in policy integration. This article seeks to understand whether and how conflict avoidance may hamper the implementation of the SDG agenda. Building on 56 interviews with policymakers and bureaucrats in Finland, Germany, and the Czech Republic, we explore how avoidance behaviours preclude the conflicts that are necessary for achieving integration. The findings suggest that avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 39 publications
(63 reference statements)
0
28
0
Order By: Relevance
“…Third, it can be observed that the pattern by which the policies for the promotion of the SDGs focus on non-conflictive synergies is being reproduced in local SSE policies. They do not tackle the possible incompatibilities among the core objectives to avoid facing possible conflicting interests among actors [16]. The explanation might be that they are at the initial stages of this kind of common co-construction process in which alliances must be built and confrontation avoided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, it can be observed that the pattern by which the policies for the promotion of the SDGs focus on non-conflictive synergies is being reproduced in local SSE policies. They do not tackle the possible incompatibilities among the core objectives to avoid facing possible conflicting interests among actors [16]. The explanation might be that they are at the initial stages of this kind of common co-construction process in which alliances must be built and confrontation avoided.…”
Section: Discussionmentioning
confidence: 99%
“…All these goals are supposed to foster changes in an integrated manner in the three dimensions of mainstream interpretations of sustainable development: social, economic, and environmental. However, this breadth and dispersion of topics means that the SDGs can be classified as an extensive "shopping list" of 17 goals, 169 targets, and 232 indicators [16], where the objectives and indicators related to the social and economic aspects predominate over those on the environment. According to Diaz-Sarachaga et al [17], of all the indicators contemplated in the UN official monitoring framework [18], 53% are from the social sphere, 24% economic, 12% environmental, and 11% from governance.…”
Section: Sdgs: Economic Growth Social Development and Ecological Sumentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, radical ideas are rarely 'fit for competition' in the bureaucratic marketplace. This may partially explain why sustainability governance is filled with changes that are not transformational in the eyes of the sustainability actors [11]; they are found to be avoiding conflicts that are too political and concrete because the competition is challenging for keeping the inter-ministerial network functional [47]. The inability to confront conflicts and adapt quickly is, however, not a phenomenon limited to the bureaucracy; in fact, large private organisations that are subjected to the brutal forces of the market of goods and services face the same challenge [48].…”
Section: Competitive Deliberationmentioning
confidence: 99%
“…Furthermore, the development of bioeconomy plays an important role in terms of the climate change with bioenergy, including biomass and waste, appearing as the major renewable energy sources (Krishnan & McCalley, 2016;Naqvi et al, 2018;Zhao et al, 2017;Zhao et al, 2017;Chen, Cheng, Nikic, & Song, 2018). Bioeconomy also is important in seeking to achieve the Sustainable Development Goals (Besi & McCormick, 2015;Lyytimäki et al, 2018;Wong & van der Heijden, 2019). The renewed EU bioeconomy strategy (EU, 2018) maximized its contribution towards the main documents-the 2030 Agenda and its Sustainable Development Goals and the Paris Agreement-and highlighted the importance of a sustainable and circular bioeconomy.…”
mentioning
confidence: 99%